Acid–base catalysis in Leuconostoc mesenteroides sucrose phosphorylase probed by site-directed mutagenesis and detailed kinetic comparison of wild-type and Glu(237)→Gln mutant enzymes - Schwarz, Alexandra (Portland Press Ltd., 2007)
The role of acid–base catalysis in the two-step enzymatic mechanism of α-retaining glucosyl transfer by Leuconostoc mesenteroides sucrose phosphorylase has been examined through site-directed replacement of the putative catalytic Glu(237) and detailed comparison of purified wild-type and Glu(237)→Gln mutant enzymes using steady-state kinetics. Reactions with substrates requiring Brønsted catalytic assistance for glucosylation or deglucosylation were selectively slowed at the respective step, about 10(5)-fold, in E237Q. Azide, acetate and formate but not halides restored catalytic activity up to 300-fold in E237Q under conditions in which the deglucosylation step was rate-determining, and promoted production of the corresponding α-glucosides. In situ proton NMR studies of the chemical rescue of E237Q by acetate and formate revealed that enzymatically formed α-glucose 1-esters decomposed spontaneously via acyl group migration and hydrolysis. Using pH profiles of k(cat)/K(m), the pH dependences of kinetically isolated glucosylation and deglucosylation steps were analysed for wild-type and E237Q. Glucosylation of the wild-type proceeded optimally above and below apparent pK(a) values of about 5.6 and 7.2 respectively whereas deglucosylation was dependent on the apparent single ionization of a group of pK(a)≈5.8 that must be deprotonated for reaction. Glucosylation of E237Q was slowed below apparent pK(a)≈6.0 but had lost the high pH dependence of the wild-type. Deglucosylation of E237Q was pH-independent. The results allow unequivocal assignment of Glu(237) as the catalytic acid–base of sucrose phosphorylase. They support a mechanism in which the pK(a) of Glu(237) cycles between ≈7.2 in free enzyme and ≈5.8 in glucosyl enzyme intermediate, ensuring optimal participation of the glutamate residue side chain at each step in catalysis. Enzyme deglucosylation to an anionic nucleophile took place with Glu(237) protonated or unprotonated. The results delineate how conserved active-site groups of retaining glycoside hydrolases can accommodate enzymatic function of a phosphorylase.